ANALISIS PEMBENTUKAN PORTOFO OPTIMAL DENGAN MENGGUNAKAN MODEL MARKOWITZ UNTUK SAHAM LQ 45 PERIODE 2008‐‐2012 - Liliana Chandra; Yudith Dyah Hapsari (Jurnal Manajemen, 2014)
The shares which are included in the LQ45 list attract investors., Make a portfolio diversification is necessary to minimize unsystematic risk. In this paper the authors wanted to construct an optimal portfolio in accordance with the theory of Markowitz. The data are taken from the yahoo.finance monthly data for stocks that are respectively included in LQ45 consistently in the period 2008 to 2012.. In establishing the optimal portfolio, the author uses the Linear Solver Microsoft Programming in Excel.Program. To determine the optimal portfolio, 17 shares which consistent listed in LQ45 in the period 2008 to 2012quired.. The Author formed 14 portfolios from the 14 stocks which have positive return. Portfolio Ewhich has the highest risk adjusted return (RAR) is selected as the optimal portfolio.